Higher plasma aldosterone is associated with increased risk of cardiovascular events in hypertensive patients with suspected OSA: UROSAH data - Gan, Lin; Li, Nanfang; Heizhati, Mulalibieke; Lin, Mengyue; Zhu, Qing; Yao, Xiaoguang; Wu, Ting; Wang, Menghui; Luo, Qin; Zhang, Delian; Jiang, Wen; Hu, Junli (Frontiers in Endocrinology, 2022)
Objective: To evaluate the association of plasma aldosterone concentration (PAC) with incident cardiovascular disease (CVD) and all-cause mortality in hypertensive patients with suspected obstructive sleep apnea (OSA) and calculate the optimal cut-off value of PAC for this specific population. Patients and methods: Participants with PAC at baseline in UROSAH in 2011-2013 were enrolled and followed up till 2021. Composite outcome included CVD and all-cause mortality. Cox proportional hazards model was used to evaluate the relationship between PAC and the composite outcome. Time-dependent ROC curve was used to determine the optimal cut-off value of PAC. Besides, we conducted subgroup analyses and sensitivity analyses. Results: 3173 hypertensive participants aged 18-84 years comprised analytical sample. During a median follow-up of 7.3 years and 22640 person-years, 69 deaths and 343 cases of incident CVD occurred. The incidence of composite outcome was increased with elevation in tertile of PAC. Compared with the first tertile, the risk of CVD and all-cause death was higher in third tertile (HR=1.81, 95%CI: 1.39-2.35, P<0.001). Time-dependent ROC curve showed optimal threshold for PAC was 12.5ng/dl. Whether renin was suppressed or not (≤0.5 or >0.5ng/ml per h), elevated PAC was associated with an increased risk of CVD. Our results remained stable and consistent in sensitivity analyses. Conclusion: Higher PAC was associated with increased risk of CVD and all-cause mortality in hypertensives with suspected OSA, even in the absence of primary aldosteronism (PA). Hypertensives with PAC≥12.5ng/dl showed a significantly increased risk of CVD, indicating that special attention and treatment were required in this specific population.